Hearing and doing the Word the drama of evangelical hermeneutics in honor of Kevin J. Vanhoozer - Vanhoozer, Kevin J. 1957-; Treier, Daniel J. 1972-; Sweeney, Douglas A. 1965- (London, UK New York, NY, USA T&T Clark, 2021)
"Kevin J. Vanhoozer is today's leading evangelical theologian of biblical interpretation. He is one of the most influential voices in contemporary hermeneutics, and in academic theology he is one of his generation's most influential evangelicals. This collection of essays honours Vanhoozer by representing the current state of evangelical hermeneutics in light of his work. The volume consists of three parts: The Biblical Script, Great Performances and Theodrama Today; each of these sections contains contributions from great scholars, who address and emphasize Kevin J. Vanhoozer's influence and impact on the history of hermeneutics"--
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Hermeneutics; Evangelicalism